Persoalan Otentitas Hadis Perspektif Ignaz Golziher - Syarifuddin, Syarifuddin; Rosyid, Moh Zaiful (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2019)
The hadith is manifested on form real in life, word, behaviours and attitude of the Prophet towards all things, sometimes its own law that is not found in the Qur’an. The existence of hadith which a central among Muslims became targets for Islam’s enemies (including orientalists) to undermine its guidelines. The Study and research of the hadith continues to be done as basis for doubting the validity of the of the hadith’s, Goldziher as one of the oriental figures who did conducted a study of hadith by continously storming the validity of the hadith with doubting authenticity of the prophet’s hadith